HIZBUT-TAHRIR IN DA'WAH AND ISLAMIC POLITICAL MOVEMENTS IN INDONESIA - Sabara Nuruddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2017)
This paper reviews Hizb ut-Tahrir in the landscape of Islamic da'wah and political movements in Indonesia. The discussion is divided into four sections: Hizbut Tahrir and the trans-national Islamic movements in Indonesia, Hizb ut-Tahrir as a form of Islamic political consciousness, Hizb ut-Tahrir as a da'wah and political movement and its khilafah as a challenge to Negara Kesatuan Republik Indonesia (NKRI-the Unitary State of the Republic of Indonesia) concept. As a trans-national movement, Hizbut-Tahrir spread through three major aspects i.e. social movements, education and da'wah, as well as through publications and the internet. Hizbut Tahrir in Indonesia then becomes a mass organization with its official name Hizbut Tahrir Indonesia (HTI). HT is a model of Islamic political awareness based on the blueprint of the past government model of khilafah ala minhajun nubuwwah. The awareness of political Islam is strongly based on a response to the condition of Muslims and Islamic countries experiencing a downturn and under the control of Western dominations and hegemonies after the colonialism era. Based on this, the presence of HTI in Indonesia cannot be separated from movements carrying the mission of siyasah (politic) to achieve the HTI’s goal of Khilafah Islamiyah. In order to realize the goal, the HT movements choose parliamentary paths through door to door dakwah in the form of halaqah. Khilafah and NKRI (Pancasila) are two diametrically different concepts. HTI Movements in Indonesia of course will receive a resistance, even be considered as "a latent danger" that threaten the existence of NKRI and Pancasila. The idea of enforcing Khalifah Islamiyah as a political struggle will certainly challenge the existence of NKRI and Pancasila as the ideology of the Republic of Indonesia. The concept of Khilafah Islamiyah is essentially 180 degrees different to the concept of NKRI and Pancasila.